Erythropoietin, Forkhead Proteins, and Oxidative Injury: Biomarkers and Biology. (2009) - Maiese, Kenneth; Hou, Jinling; Chong, Zhao Zhong; Shang, Yan Chen
Abstract : Oxidative stress significantly impacts multiple cellular pathways that can lead to the initiation and progression of varied disorders throughout the body. It therefore becomes imperative to elucidate the components and function of novel therapeutic strategies against oxidative stress to further clinical diagnosis and care. In particular, both the growth factor and cytokine erythropoietin (EPO), and members of the mammalian forkhead transcription factors of the O class (FoxOs), may offer the greatest promise for new treatment regimens, since these agents and the cellular pathways they oversee cover a range of critical functions that directly influence progenitor cell development, cell survival and degeneration, metabolism, immune function, and cancer cell invasion. Furthermore, both EPO and FoxOs function not only as therapeutic targets, but also as biomarkers of disease onset and progression, since their cellular pathways are closely linked and overlap with several unique signal transduction pathways. Yet, EPO and FoxOs may sometimes have unexpected and undesirable effects that can raise caution for these agents and warrant further investigations. Here we present the exciting as well as the complex role that EPO and FoxOs possess to uncover the benefits as well as the risks of these agents for cell biology and clinical care in processes that range from stem cell development to uncontrolled cellular proliferation.